2012
DOI: 10.7314/apjcp.2012.13.12.6277
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year Study of Esophageal Cancer in Guilan Province, Iran: The Guilan Cancer Registry Study (GCRS)

Abstract: Background: Northern Iran counts as one of the highest prevalence regions for esophageal cancer (EC) worldwide. This study was designed to assess the epidemiologic aspects of EC in north central and northwest Iran over a 10 year period. Materials and Methods: The Guilan cancer registry study (GCRS) is a populationbased cancer registry study featuring retrospective (1996-2003) and prospective (2004-2005) phases. A detailed questionnaire based on WHO standards for cancer registratration was applied to gather the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…However, the incidence of esophageal cancer is low in western countries compared to Asian countries (Bloomfled et al, 2006). The high rates of esophageal cancer in the northern part of Afghanistan reflected that this area lies in Central Asian Esophageal Cancer Belt (Mir et al, 2009;Mansour-Ghanaei et al, 2012). This shows the variable geographic distribution of esophageal cancer which might due to many known and unknown environmental and ethnic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of esophageal cancer is low in western countries compared to Asian countries (Bloomfled et al, 2006). The high rates of esophageal cancer in the northern part of Afghanistan reflected that this area lies in Central Asian Esophageal Cancer Belt (Mir et al, 2009;Mansour-Ghanaei et al, 2012). This shows the variable geographic distribution of esophageal cancer which might due to many known and unknown environmental and ethnic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were published from 1968 to 2017. Based on geographical locations, four studies were conducted in all states of Iran [24][25][26][27], three in Fars province [28][29][30], three in East Azerbaijan [15,31,32], two in Ardabil province [33,34], two in Guilan province [35,36], two in Golestan province [37,38], one in Kerman province [39], one in Semnan province [40], one in Tehran metropolis [41], one in Mazandaran province [42], one in Caspian littoral [43] and one in Shahroud city [44]. All the studies have reported ASRs.…”
Section: (A) Description Of Literature Searchmentioning
confidence: 99%
“…Some parts of Iran, which have common borders with Turkmenistan and Afghanistan countries, experience much higher incidence rates of this cancer. These regions include Mazandaran, Golestan, and Khorasan provinces [14,35].…”
Section: Forest Plot Of the Random-effect Meta-analysis For Asrs Ofmentioning
confidence: 99%
“…In 50-60% of cases, ESCC is located in the middle third thoracic esophagus in Thailand, Iran, and Japan [3,12,13,14]. About 60% of SCCs is also located in the middle third of the esophagus in Iran.…”
Section: Location Of Escc and Eacmentioning
confidence: 99%